Fluctuations and localization in mesoscopic electron systems - Janssen, Martin (World Scientific, 2001)
The quantum phenomena of tunnelling and interference show up not only in the microscopic world of atoms and molecules, but also in cold materials of the real world, such as metals and semiconductors. Though not fully macroscopic, such "mesoscopic" systems contain a huge number of particles, and the holistic nature of quantum mechanics becomes evident already in simple electronic measurements. The measured quantity fluctuates as a function of applied fields in an unpredictable, yet reproducible way. Despite this fingerprint character of fluctuations, their statistical properties are universal, ie. they are the same for a large class of different mesoscopic systems, having only very few parameters in common. Localization of electrons is a dramatic effect of destructive interference. As a consequence a metal can become an insulator while reaching mesoscopic scales.